Dr. Richard Heinzl: At the Forefront of Global Healthcare - Sorouri, Kimia (The Meducator, 2012)
Dr. Richard Heinzl is a McMaster Medical School alumni. He also studied at Harvard and Oxford University, where he received Master degrees in Public Health and Science, respectively. Dr. Heinzl was connected to McMaster University prior to becoming a student himself as his father, Rudy Heinzl, was the Dean of Student Affairs for 11 years. Dr. Heinzl founded the Canadian chapter of Médicins Sans Frontières only a year after graduating from Medical School. When he is not abroad practicing medicine or performing research, Dr. Heinzl often returns to McMaster to share his immense knowledge and life experiences. His most recent presentation at McMaster on October 19th was organized by the Medical School community. During this presentation, Dr. Heinzl shared key aspects of a health plan he is constructing for the Kalinago people of Dominica.